2015
DOI: 10.1007/s12010-015-1880-z
|View full text |Cite
|
Sign up to set email alerts
|

Monascus: a Reality on the Production and Application of Microbial Pigments

Abstract: Monascus species can produce yellow, orange, and red pigments, depending on the employed cultivation conditions. They are classified as natural pigments and can be applied for coloration of meat, fishes, cheese, beer, and pates, besides their use in inks for printer and dyes for textile, cosmetic, and pharmaceutical industries. These natural pigments also present antimicrobial activity on pathogenic microorganisms and other beneficial effects to the health as antioxidant and anticholesterol activities. Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 78 publications
3
61
0
Order By: Relevance
“…Nonetheless, the vast majority of authors estimate pigment production by this method, with pigment production ranging from hundreds of absorbance units/mL culture media in SmF, for example, 220 OD 510 /mL in optimized conditions by Kim et al [100,123], to thousands of absorbance units/g dry substrate in SSF, for example, 5430 OD 500 /g dry matter [22]. The best procedure for pigment analysis is probably liquid chromatography, which allows separation and quantification of individual pigments; using this method, Hajjaj et al [80] considered one unit OD 480 correspondent to 15mg/L of red pigment with M = 498 g/mol.…”
Section: Pigment Analysis Methods and Amounts Producedmentioning
confidence: 99%
“…Nonetheless, the vast majority of authors estimate pigment production by this method, with pigment production ranging from hundreds of absorbance units/mL culture media in SmF, for example, 220 OD 510 /mL in optimized conditions by Kim et al [100,123], to thousands of absorbance units/g dry substrate in SSF, for example, 5430 OD 500 /g dry matter [22]. The best procedure for pigment analysis is probably liquid chromatography, which allows separation and quantification of individual pigments; using this method, Hajjaj et al [80] considered one unit OD 480 correspondent to 15mg/L of red pigment with M = 498 g/mol.…”
Section: Pigment Analysis Methods and Amounts Producedmentioning
confidence: 99%
“…Bühler et al (2015) reported that during cultivation of M. ruber, both pigment and biomass were higher under red light than in dark but highly inhibited by direct exposure to white light. Wang et al (2015) also reported that monascin production increased by about 15 to 27% when grown under blue light of different intensities and durations while Velmurugan et al (2010) reported that even yellow light inhibited both pigment and biomass production by M. purpureus.…”
Section: Effect Of Light On Pigment Production By Filamentous Fungimentioning
confidence: 99%
“…Production of fungal pigments is affected by both Ogbonna et al 961 nutritional and environmental factors. Some review articles on production and uses of fungal pigments (Dufosse et al, 2014;Chen et al, 2015;AbdelGhany, 2015;Vendruscolo et al, 2015) have shown that fungi are major sources of renewable and reliable natural food colourants. However, commercial production of these pigments requires good understanding of the factors that affect their production.…”
Section: Introductionmentioning
confidence: 99%
“…Common fungal pigments detected belong to the group of melanins, carotenoids, lycopene and xanthophylls [8,9,10,11]. These pigments offer protection to fungi and show diverse biological activity [12,13]. With globalization, there is an increasing trend for products with natural and safe pigments.…”
Section: Introductionmentioning
confidence: 99%